HISTORICAL-CRITICAL HERMENEUTICS OF AL-JABIRI: REDEFINITION AND RECONSTRUCTION OF CONTEMPORARY UNDERSTANDING OF THE QUR'AN - Ahmad Tri Muslim HD; Harel Bayu Paizin; Muh. Alimin; Syamsul Ma’arif Ilyas (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2025)
This study examines al-Jābirī's interpretive reasoning as an effort to reconstruct the understanding of the Qur'an. Stemming from the inevitability of the dynamics of Qur'anic interpretation and the problems of turats (heritage), this study positions al-Jābirī as a figure who bridges tradition and Western modernity in his thought. This library research employs a biographical study model, with data drawn from written literature, particularly two of al-Jābirī's works on tafsir: Madkhāl ilā al-Qur’ān al-Karīm and Faḥm al-Qur’ān al-Ḥakīm: al-Tafsīr al-Wāḍiḥ Ḥasb Tartīb al-Nuzūl. To delve into al-Jābirī's interpretive thought, a theoretical-objective hermeneutic theory is utilized with two approaches: psychological (understanding al-Jābirī's character through his life background, geographical, socio-political context, and intellectual journey) and linguistic (specifically reading al-Jābirī's works). In his tafsir, al-Jābirī redefines the Qur'an as al-Ẓāhirah al-Qur’āniyyah (the Qur'anic phenomenon), which encompasses timeless, spiritual, and social da'wah elements, rejecting definitions that are ideologically laden and ahistorical. Al-Jābirī's interpretive methodology applies the principles of al-faṣl (separation of the reader from the object of reading for objectivity) and al-waṣl (reuniting the reader with the object of reading for contemporary relevance). Finally, al-Jābirī promotes Tafsir Nuzūlī (chronological interpretation) which emphasizes the logical relationship between the historicity of Muhammad's da'wah journey and the Qur'anic verses as responses, with mapping based on the Meccan and Medinan periods. This aims to make the Qur'an speak and introduce itself, while also remaining relevant to contemporary times.